Les stratégies d’adaptation de quelques tragédies de Pierre Corneille dans le courant classiciste en Pologne (XVIIIe et XIXe siècles) - Bajer, Michał (Studia Romanica Posnaniensia, 2014)
The study discusses general rules of transforming Pierre Corneille’s texts in the transposition process, so as to fit the linguistic and cultural context of Polish classicism. The analysis concerns translations and adaptations following the first reception period of Corneille’s works in seventeenth-century Poland. These include: “Otto” by Stanisław Konarski, “Herakliusz” by Tomasz Aleksandrowicz from the years 1744-1749 (the second Polish reception period of Corneille’s works), “Cynna” by Franciszek Godlewski, as well as “Cynna” and “Horacjusze” by Ludwik Osiński from the years 1802-1808 (the third reception period). In the 18th century, the strategy of emphasizing didactic elements of texts is dominant. In 19th century, the authors strengthen suspense and the element of surprise; Aleksandrowicz uses prose and Osiński simplifies classical rhetoric. All of the translators share the ambition of enriching the Polish language and creating the tragic canon.